BAURAN PEMASARAN DAN PENGARUHNYA TERHADAP MINAT NASABAH UNTUK MENABUNG DI TAMPAN BANK SULSELBAR - Bulan, Syari (Jurnal Minds: Manajemen Ide dan Inspirasi, 2018)
This study aims to analyze the influence of savings product factors, interest rates, location, promotion and bank services to customers in choosing TAMPAN at PT. Bank Sulselbar, Tbk Main Branch of Makassar. The research data was collected using questionnaires which distributed to 100 customers of PT Bank Sulselbar, Tbk Makassar Main Branch. Data collected were analyzed using descriptive analysis and multiple regression analysis. The results of this study indicate the influence of savings products, interest rates, location, promotion and service affect the customer in choosing TAMPAN at PT. Bank Sulselbar, Tbk Main Branch of Makassar. This means that marketers, in this case PT Bank Sulselbar, Tbk Makassar Branches should need to consider these five things in marketing their savings products.